Оптимізація системи регулювання витрати стічних вод в абсорбційно-біохімічній установці - Tarhonii, Ivan; Сафоник, Андрій; Трохимчук , Максим; Ластовецький, Дмитро (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Проведено аналіз факторів, що впливають на якість очищення стічних вод в абсорбційно-біохімічній установці. Розроблено оптимізовану систему регулювання витрати стічних вод процесу їх очищення, що забезпечує компенсацію збурення, а саме нерівномірності розподілу вхідної концентрації забруднення. <pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" data-placeholder="Переклад" data-ved="2ahUKEwjTnN_xnKKJAxXGUXcKHbl0IfUQ3ewLegQIBxAU" aria-label="Перекладений текст: an analysis of factors affecting the quality of wastewater treatment in the absorption-biochemical installation was carried out. An optimized system for regulating the flow of wastewater in the process of its treatment has been developed, which provides compensation for the disturbance, namely the unevenness of the distribution of the input concentration of pollution.">An analysis of factors affecting the quality of wastewater treatment in the absorption-biochemical installation was carried out. An optimized system for regulating the flow of wastewater in the process of its treatment has been developed, which provides compensation for the disturbance, namely the unevenness of the distribution of the input concentration of pollution.